2021
DOI: 10.1186/s12913-021-06480-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric non-urgent emergency department visits and prior care-seeking at primary care

Abstract: Background We aimed to examine how caregiver perceptions of primary care affects care-seeking prior to pediatric non-urgent ED visits. Methods We performed a cross-sectional survey of caregivers of children presenting to a pediatric ED during weekday business hours and triaged as low acuity. We first compared caregiver sociodemographic characteristics, perceptions of primary care, and stated preference in care sites (ED vs PCP) for caregivers who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In another study, it was found that lower educational attainment levels were associated with not seeking primary care physician care before presenting to the ED. 15 Akbayram and Coskun 13 also found that fathers with lower education levels preferred other specialists over family physicians. On the other hand, Burokiene et al 20 showed that more educated parents and parents with a higher income were more likely to bring their child to ED without visiting a primary care physician.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In another study, it was found that lower educational attainment levels were associated with not seeking primary care physician care before presenting to the ED. 15 Akbayram and Coskun 13 also found that fathers with lower education levels preferred other specialists over family physicians. On the other hand, Burokiene et al 20 showed that more educated parents and parents with a higher income were more likely to bring their child to ED without visiting a primary care physician.…”
Section: Discussionmentioning
confidence: 97%
“…In that study, onset of child's complaints outside working hours was the most common reason among high school or university graduate mothers. In another study, it was found that lower educational attainment levels were associated with not seeking primary care physician care before presenting to the ED 15 . Akbayram and Coskun 13 also found that fathers with lower education levels preferred other specialists over family physicians.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations